Switchable Supercapacitors with Transistor-Like Gating Characteristics (G-Cap) - Lochmann, Stefanie; Braeuniger, Yannik; Gottsmann, Vincent; Galle, Lydia; Grothe, Julia; Kaskel, Stefan (Advanced Functional Materials, 2020)
A novel three-electrode electrolyte supercapacitor (electric double-layer capacitor [EDLC]) architecture in which a symmetrical interdigital “working” two-electrode micro-supercapacitor array (W-Cap) is paired with a third “gate” electrode that reversibly depletes/injects electrolyte ions into the system controlling the “working” capacity effectively is described. All three electrodes are based on precursor-derived nanoporous carbons with well-defined specific surface area (735 m2 g−1). The interdigitated architecture of the W-Cap is precisely manufactured using 3D printing. The W-Cap operating with a proton conducting PVA/H2SO4-hydrogel electrolyte and high capacitance (6.9 mF cm−2) can be repeatedly switched “on” and “off”. By applying a low DC bias potential (−0.5 V) at the gate electrode, the AC electroadsorption in the coupled interdigital nanoporous carbon electrodes of the W-Cap is effectively suppressed leading to a stark capacity drop by two orders of magnitude from an “on” to an “off” state. The switchable micro-supercapacitor is the first of its kind. This general concept is suitable for implementing a broad range of nanoporous materials and advanced electrolytes expanding its functions and applications in future. The integration of intelligent functions into EDLC devices has extensive implications for diverse areas such as capacitive energy management, microelectronics, iontronics, and neuromodulation.
CRIS-Team Scopus Importer:2022-04-14
Keywords: 3D printing; gating; micro-supercapacitors; nanoporous carbon; supercapacitors